Coptisine Inhibits Influenza Virus Replication by Upregulating p21 - Ming-Feng He; Jian-Hui Liang; Yan-Ni Shen; Chao-Wei Zhang; Kuang-Yang Yang; Li-Chu Liu; Qian Xie; Chun Hu; Xun Song; Yan Wang (Molecules, 2023)
The activation of innate antiviral immunity is a promising approach for combatting viral infections. In this study, we screened Chinese herbs that activated human immunity and identified coptisine as a potent inhibitor of the influenza virus with an EC50 of 10.7 μM in MDCK cells. The time of an addition assay revealed that pre-treatment with coptisine was more effective at reducing viral replication than co-treatment or post-treatment. Our bulk RNA-sequencing data showed that coptisine upregulated the p21 signaling pathway in MDCK cells, which was responsible for its antiviral effects. Specifically, coptisine increased the expression of p21 and FOXO1 in a dose-dependent manner while leaving the MELK expression unchanged. Docking analysis revealed that coptisine likely inhibited MELK activity directly by forming hydrogen bonds with ASP-150 and GLU-87 in the catalytic pocket. These findings suggest that coptisine may be a promising antiviral agent that regulates the p21 signaling pathway to inhibit viral replication.